Categorization Task over a Touch Screen in Age-Related Macular Degeneration. Issue 10 (October 2015) - Lenoble, Quentin; Tran, Thi Ha Chau; Szaffarczyk, Sébastien; Boucart, Muriel
ABSTRACT: Purpose: In our modern society, many touch screen applications require hand-eye coordination to associate an icon with its specific contextual unit on phones, on computers, or in public transport. We assessed the ability of patients with age-related macular degeneration (AMD) to explore scenes and to associate a target (animal or object) with a unique congruent scene (e.g., to match a fish with the sea) presented between three other distractors on a touch screen computer. Methods: Twenty-four patients with AMD (64 to 90 years) with best-corrected visual acuity between 20/40 and 20/400 as well as 17 age-matched (60 to 94 years) and 15 young (22 to 34 years) participants with normal visual acuity had to match a target with a congruent scene by moving their index finger on a 22-in touch screen. Results: Patients were as accurate (98.7% correct responses) as the age-matched control (98.9% correct responses) and young participants (99.3% correct responses) at performing the task. The duration of exploration was significantly longer for the AMD patients (mean, 4.13 seconds) compared with the age-matched group (mean, 2.96 seconds). The young participants were also significantly faster than the old group (mean, 0.93 seconds). The movement parameters of the older participants (patients and old control subjects) were affected compared with the young; the peak speed decreased (−8 cm/s) and the movement duration increased (+0.9 seconds) with age compared with the young group. Conclusions: People with AMD are able to perform a contextual association task on a touch screen with high accuracy. The AMD patients were specifically affected in the "exploration" phase; their accuracy and movement parameters did not differ from the old control group. Our study suggests that the decline associated with AMD is more focused on the duration of exploration than on movement parameters in touch screen use.